Mosquitoes and the city: effects of urbanization on Aedes albopictus and Culex pipiens captures in southern Spain - Garrido, Mario (2025)
Background Urbanization and land-use changes profoundly affect mosquito ecology, potentially altering species’ abundance, seasonal dynamics, and pathogen transmission risk. The invasive mosquito Aedes albopictus has rapidly expanded from Southeast Asia to temperate regions worldwide, including Europe, where it now coexists with native species such as Culex pipiens. Both are competent vectors of zoonotic pathogens and may respond differently to urban environmental gradients. Methods We assessed the impact of urbanization on mosquito populations by comparing the abundance and seasonality of Ae. albopictus and Cx. pipiens in urban and periurban areas of Granada, southern Spain, over two consecutive years (2023–2024). A total of 19 mosquito trapping sessions were conducted using BG-Sentinel traps baited with CO2 and BG-Lure, covering the main seasonal activity period. Additionally, 260 mosquito pools were screened for Dirofilaria spp. DNA using PCR. Results A total of 450 Ae. albopictus and 641 Cx. pipiens females were captured. Ae. albopictus showed a unimodal seasonal pattern, peaking from late July to late August, with a more pronounced increase in urban sites. Cx. pipiens was more abundant in periurban areas, especially during its late July peak. Generalized linear mixed models revealed significant interactions between habitat and year for Cx. pipiens: abundance declined in periurban habitats from 2023 to 2024 but remained stable in urban areas. Seasonal peaks were also more extended in periurban sites. All mosquito pools tested negative for Dirofilaria spp. Conclusions Our findings highlight species-specific responses to urbanization, with Ae. albopictus favoring urban environments and Cx. pipiens thriving in periurban zones. These patterns underscore the need for habitat- and species- specific vector surveillance and control strategies. Urban control efforts should target early summer Ae. albopictus peaks, particularly around artificial breeding sites, while periurban interventions should focus on Cx. pipiens populations that persist later in the season. The absence of Dirofilaria DNA suggests low current transmission, but continued molecular surveillance is warranted, particularly in periurban areas where high densities of Cx. pipiens vectors and animal reservoirs may overlap under changing environmental conditions.